Family ties, incentives and development: A model of coerced altruism - Ingela Alger; Jörgen W. Weibull (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
We analyze the effects of family ties on the incentives for production of effort, where family ties are defined as a mixture of true and coerced altruism between family members. We model families as pairs of siblings. Each sibling exerts effort in order to obtain output under uncertainty. A social norm dictates that a sibling with a high output must share a specified amount of this output with his sibling, if the latter's output is low. Siblings may be truly altruistic towards each other, but not to a larger degree than dictated by the social norm. We compare such informal family insurance with actuarially fair formal insurance. We show that coerced family altruism reduces individual efforts in equilibrium. However, individuals always benefit ex ante from living in families with coerced altruism, as compared with living in autarky. We show that a certain degree of coerced family altruism is robust as a social norm in a society of selfish individuals. Finally, we show that if family members are sufficiently altruistic to each other, then informal family insurance by way of coerced altruism may outperform actuarially fair insurance programs.
Keywords: D02; D13; 330; altruism; coerced altruism; family ties; insurance; moral hazard; Familie; Altruismus; Soziales Verhalten; Soziale Norm; Moral Hazard; Versicherungsschutz; Theorie